Vinyl-containing self-assembly material and application thereof
By using self-assembled small molecule materials containing vinyl groups and forming a stable film through cross-linking reaction, the problem of instability of the SAM hole transport layer film is solved, and the stability and photoelectric properties of the organic solar cell are significantly improved.
Patent Information
- Application Number
- CN202411709048.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The hole transport layer based on SAM molecules is usually a very thin single-molecular layer, which makes it difficult to form a uniform and stable film during preparation. Its photoelectric performance life is short, limiting its commercialization process in organic solar cell devices.
A self-assembled small molecule material containing vinyl group is provided to form a uniformly stable thin film by cross-linking, and is applied to organic solar cell devices as a hole selection layer.
The dense and uniform film is formed through cross-linking reaction, which significantly improves the stability and photoelectric life of the organic solar cell.
Smart Images

Figure CN119684357A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell materials, and in particular to a self-assembly material containing vinyl groups and application thereof. Background Art
[0002] Organic solar cells have attracted much attention due to their flexibility, light weight, and ability to be printed to prepare large-area devices. Currently, the energy conversion efficiency of single-junction devices has exceeded 20%, showing its huge application potential. Organic solar cells adopt a "sandwich" layer-by-layer stacking structure, with a hole transport layer and an electron transport layer on both sides of the active layer, which are used to modify the work function of the electrode, reduce the recombination of charges at the interface, and thus improve device performance.
[0003] Currently, PEDOT:PSS has been widely used as a hole transport layer material in organic solar cells. However, due to its strong acidity and hygroscopicity, PEDOT:PSS has poor stability. In addition, PEDOT:PSS has absorption in the infrared region and a high HOMO energy level, which limits the short-circuit current density (J SC ) and open circuit voltage (V OC ) enhancement.
[0004] Self-assembled monolayers (SAMs) containing anchoring groups have attracted extensive attention due to their advantages such as low production cost, negligible optical and electrical losses, easy adjustment of energy levels and surface properties, conformal coverage on rough surfaces, and simple deposition on large-area substrates. The structure of SAM molecules usually consists of three parts: an end group with hole transport function, an anchoring group that can be chemically adsorbed on the substrate, and a bridging group between the two.
[0005] For example, CN 116655682 A discloses a self-assembled monolayer hole transport material based on diphenylamine and its synthesis method, as well as its application in inverted perovskite solar cells. Diphenylamine with good hole transport properties is used as the parent core to ensure the hole transport performance of the material; by adjusting the contact groups at the interface between diphenylamine and perovskite, the interface dipole and passivation performance are regulated; and by the butyl phosphate anchoring group, the material is completely covered on the substrate surface and self-assembled stably. When the material is used as a hole transport layer in an inverted perovskite solar cell, a photoelectric conversion efficiency of >21% can be obtained without doping, and it has broad application prospects.
[0006] CN116874529A discloses a self-assembled monolayer hole transport material based on an alkyl polyphosphate anchoring group and a synthesis method thereof, as well as an application in an inverted perovskite solar cell. With carbazole or 3,6-diphenylcarbazole having good hole transport properties as the parent core, the anchoring group is improved from the traditional alkyl monophosphate to alkyl diphosphate and triphosphate, so as to achieve complete coverage and stable self-assembly of the material on the substrate surface.
[0007] However, the hole transport layer based on SAM molecules is usually a very thin monolayer, which makes it difficult to form a uniform and stable film during preparation. Its photoelectric performance life is short, which limits its commercialization process in organic solar cell devices. Summary of the invention
[0008] Based on the problem of insufficient photoelectric stability of hole transport materials, the present invention provides a self-assembled small molecule material containing vinyl. When the self-assembled small molecule material is used as a hole selection layer material in an organic solar cell device, it can form a uniform and stable film by cross-linking, thereby improving the stability of the device.
[0009] To achieve the above object, the technical solution adopted by the present invention is: A self-assembly material containing vinyl groups, wherein the self-assembly material has a structure as shown in formula (I): (I) in: n is selected from 0, 1, 2, 3, 4, 5 or 6; -Z- is selected from the group consisting of absence, a single bond, -O-, -S-, or CR1R2; R1 and R2 are independently selected from -H, -D, and an alkyl group having 1 to 6 carbon atoms.
[0010] In some embodiments, n is selected from 1 or 3, and the self-assembling material containing vinyl groups has the following general structure: .
[0011] In some embodiments, -Z- is selected from absent, a single bond, -O-, -S-, or C(CH3)2.
[0012] Furthermore, R1 and R2 are independently selected from -H, -D, methyl, ethyl, n-propyl, isopropyl, n-butyl or tert-butyl.
[0013] In some embodiments, the self-assembling material is selected from any one of the following structures:
[0014]
[0015] .
[0016] The present invention also provides an organic solar cell, which comprises at least one hole selection layer, wherein the hole selection layer material comprises the vinyl-containing self-assembly material as described above.
[0017] The vinyl groups in the self-assembly material of the present invention can undergo self-crosslinking under heating conditions, thereby making the prepared hole selection layer dense and uniform, thereby improving the photoelectric stability of the organic solar cell.
[0018] In some embodiments, the organic solar cell comprises an anode layer, a hole selection layer, a photoactive layer, an electron transport layer and a cathode layer stacked sequentially from bottom to top, and the material of the hole selection layer is selected from the self-assembled material containing vinyl as described above.
[0019] In some embodiments, the material of the anode layer is selected from FTO or ITO; In some embodiments, the photoactive layer comprises a donor material and an acceptor material, wherein the donor material is preferably selected from one or more of PBDB-T, PM6, PM7, D18, D18-Cl, PBQx-Cl, PTQ10, but is not limited thereto; the acceptor material is selected from Y6, L8-BO, N3, BTP-eC9, PC 61 BM, PC 71 One or more of BM, but not limited thereto; In some embodiments, the mass ratio of the donor material to the acceptor material in the photoactive layer is selected from 0.8:1.8 to 1.8:0.8. Further, the mass ratio is 1:1 to 1:1.8; further, the mass ratio is 1:1 to 1:1.5; further, the mass ratio is 1:1 to 1:1.2.
[0020] In some embodiments, the material of the electron transport layer is selected from one or more of PDINN, PDINO, PFN-Br, PNDIT-F3N-Br or PNDIT-F3N, but is not limited thereto.
[0021] In some embodiments, the cathode layer material is selected from zinc (Zn), silver (Ag), aluminum (Al), gold (Au), nickel (Ni), or alloys of the above metals.
[0022] Furthermore, the organic solar cell further comprises a substrate. In one embodiment, the substrate is disposed on one side of the anode and on a different side from the active layer. In another embodiment, the substrate is disposed on one side of the cathode and on a different side from the active layer.
[0023] In one embodiment, as a substrate, a substrate having excellent transparency, surface smoothness, ease of handling, and water resistance can be used. Specifically, a glass substrate, a thin film glass substrate, or a transparent plastic substrate can be used. The plastic substrate may include a film in a single-layer or multi-layer form, such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyetheretherketone (PEEK), polyimide (PI), polyparaxylene (Parylene), etc., but is not limited thereto, and a substrate commonly used for organic solar cells may also be used.
[0024] In order to improve the performance of the organic solar cell device of the present invention, the organic solar cell may further comprise other functional layers.
[0025] The present invention also provides a method for preparing the organic solar cell, comprising the steps of: Step 1, cleaning the conductive glass containing the anode layer; Step 2: dissolving the self-assembly material containing vinyl as described above in an organic solvent to prepare a hole selection layer solution, and evenly spin-coating the hole selection layer solution on the conductive glass containing the anode layer, and standing for reaction at 100-150° C. for 5-20 min to obtain a hole selection layer; Step 3, spin coating a photoactive material on the surface of the hole selection layer under an inert atmosphere to prepare a photoactive layer, and annealing; Step 4: Spin coating the electron transport layer material on the photoactive layer to obtain the electron transport layer; Step 5: Under a vacuum environment, a cathode material is evaporated on the surface of the electron transport layer to obtain a cathode layer, and the organic solar cell is obtained by packaging.
[0026] More specifically, the present invention also provides a method for preparing the organic solar cell, comprising the following steps: Step 1: Clean the ITO conductive glass with detergent, rinse it, and then ultrasonically clean it with deionized water, acetone, and isopropanol for 10-20 minutes, then blow it dry with nitrogen and treat it in a plasma cleaner for 1-10 minutes.
[0027] Step 2: Dissolve the self-assembly material containing vinyl in methanol or ethanol to prepare a hole selection layer solution, wherein the concentration of the self-assembly material containing vinyl in methanol or ethanol is 0.2-1 mg / ml. The hole selection layer solution is evenly spin-coated on the ITO conductive glass, the spin-coating speed is 2000-4000 rpm / min, and the spin-coating time is 20-40s to obtain a hole selection layer. The device prepared with the hole selection layer is placed on a hot stage at 100-150°C for 5-20 minutes to react so that a cross-linking reaction occurs.
[0028] Step 3: In a glove box (inert gas atmosphere), the photoactive layer material is evenly spin-coated on the hole transport layer at a rotation speed of 1800-4000 rpm to obtain a photoactive layer.
[0029] Step 4: After thermal annealing on a hot plate at 80-120° C. for 5-20 min, the electron transport layer material is evenly spin-coated on the photoactive layer at a spin coating speed of 1800-4000 rpm to obtain the electron transport layer.
[0030] Step 5: In high vacuum (1×10 -6 The cathode material is evaporated onto the electron transport layer in a pressure of 1000 mbar to obtain a cathode layer.
[0031] Step 6: The device is encapsulated with UV-curable resin in a nitrogen glove box.
[0032] The present invention also provides the application of the organic solar cell in automobiles, buildings or Internet of Things devices. Photovoltaics include but are not limited to automobile and building integrated photovoltaics, indoor photovoltaics, marine photovoltaics, etc.
[0033] Compared with the prior art, the present invention has the following beneficial effects: The vinyl-containing self-assembly material of the present invention can undergo a cross-linking reaction under heating conditions to form a dense, uniform and morphologically stable film, thereby greatly improving the stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of the organic solar cell device prepared in Application Examples 1-6 and Comparative Application Example 1.
[0035] Figure 2 T80 curves of the organic solar cells prepared in Application Example 1 and Comparative Application Example 1. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0037] Example 1 Synthesis of Compound (3)
[0038] Synthesis of compound 3-3: Accurately weigh compound 3-1 (658 mg, 3 mmol) and compound 3-2 (22.6 g, 120 mmol), add tetrabutylammonium bromide (97 mg, 0.3 mmol) and 8 ml of 50% potassium hydroxide aqueous solution into a 100 ml three-necked flask, replace nitrogen three times, raise the temperature to 70 ° C, and react for 3 hours. After the reaction solution is cooled to room temperature, it is poured into water for quenching, extracted with ethyl acetate, and the organic phase is distilled under reduced pressure to remove excess solvent. The crude product is purified by column chromatography (PE: EA = 8: 1 (volume ratio)) to obtain about 782 mg of compound 3-3, with a yield of 79.8%. MALDI-TOF-MS: 326.52.
[0039] Synthesis of compound 3-4: Accurately weigh compound 3-3 (653 mg, 2 mmol), add it to a 25 ml three-necked flask, add 10 ml of triethyl phosphite to dissolve it, and react it in an oil bath preheated to 160°C for 1 hour. Remove triethyl phosphite by vacuum distillation, and then purify it by column chromatography (PE: EA = 1: 2 (volume ratio)) to obtain about 739 mg of compound 3-4, with a yield of 96.5%. MALDI-TOF-MS: 383.11.
[0040] Synthesis of compound (3): Accurately weigh compound 3-4 (383 mg, 1 mmol), add it to a 25 ml three-necked flask, add 10 ml of anhydrous 1,4-dioxane to dissolve, replace nitrogen three times, slowly add 3 ml of trimethylsilyl bromide, and then raise the temperature to 70 ° C for 2 hours. Remove excess solvent by vacuum distillation, then add methanol to dissolve the product and transfer it to a beaker, add appropriate amount of water until solid precipitates, stir for 30 minutes and filter. Obtain about 248 mg of compound (3), yield: 75.6%. MALDI-TOF-MS: 327.85.
[0041] Example 2: Synthesis of Compound (4)
[0042] Synthesis of compound 4-2: Accurately weigh compound 3-1 (658 mg, 3 mmol) and compound 4-1 (25.9 g, 120 mmol), add tetrabutylammonium bromide (97 mg, 0.3 mmol) and 8 ml of 50% potassium hydroxide aqueous solution into a 100 ml three-necked flask, replace nitrogen three times, raise the temperature to 70 ° C, and react for 3 h. After the reaction solution is cooled to room temperature, it is poured into water for quenching, extracted with ethyl acetate, and the organic phase is distilled under reduced pressure to remove excess solvent. The crude product is purified by column chromatography (PE: EA = 10: 1 (volume ratio)) to obtain about 821 mg of compound 4-2, with a yield of 77.2%. MALDI-TOF-MS: 354.35.
[0043] Synthesis of compound 4-3: Accurately weigh compound 4-2 (709 mg, 2 mmol), add it to a 25 ml three-necked flask, add 10 ml of triethyl phosphite to dissolve it, and react it in an oil bath preheated to 160 ° C for 1 hour. Remove triethyl phosphite by vacuum distillation, and then purify it by column chromatography (PE: EA = 1: 2 (volume ratio)) to obtain about 785 mg of compound 4-3, with a yield of 95.3%. MALDI-TOF-MS: 411.74.
[0044] Synthesis of compound (4): Accurately weigh compound 4-3 (412 mg, 1 mmol), add it to a 25 ml three-necked flask, add 10 ml of anhydrous 1,4-dioxane to dissolve, replace nitrogen three times, slowly add 3 ml of trimethylsilyl bromide, and then raise the temperature to 70 ° C for 2 hours. Remove excess solvent by vacuum distillation, then add methanol to dissolve the product and transfer it to a beaker, add appropriate amount of water until solid precipitates, stir for 30 minutes and filter. Obtain about 273 mg of compound (4), yield: 76.7%. MALDI-TOF-MS: 355.94.
[0045] Example 3: Synthesis of Compound (5)
[0046] Synthesis of compound 5-2: Accurately weigh compound 5-1 (1.02g, 3mmol), compound 3-2 (22.6g, 120mmol), add tetrabutylammonium bromide (97mg, 0.3 mmol), 8ml 50% potassium hydroxide aqueous solution into a 100ml three-necked flask, replace nitrogen three times, raise the temperature to 70℃, and react for 3 hours. After the reaction solution is cooled to room temperature, it is poured into water for quenching, extracted with ethyl acetate, and the organic phase is distilled under reduced pressure to remove excess solvent. The crude product is purified by column chromatography (PE:EA=10:1 (volume ratio)) to obtain about 982mg of compound 5-2 with a yield of 73.0%. MALDI-TOF-MS: 448.25.
[0047] Synthesis of compound 5-3: Accurately weigh compound 5-2 (896 mg, 2 mmol), add it to a 25 ml three-necked flask, add 10 ml of triethyl phosphite to dissolve it, and react it in an oil bath preheated to 160 ° C for 1 hour. Remove triethyl phosphite by vacuum distillation, and then purify it by column chromatography (PE: EA = 1: 2 (volume ratio)) to obtain about 871 mg of compound 5-3, with a yield of 86.2%. MALDI-TOF-MS: 505.38.
[0048] Synthesis of compound 5-5: Accurately weigh compound 5-3 (758 mg, 1.5 mmol) and bistriphenylphosphine palladium dichloride (77 mg, 0.11 mmol) into a 50 ml three-necked flask, add 20 ml toluene and stir to dissolve, replace nitrogen three times, stir to react for 15 minutes, then add compound 5-4 (1.14 g, 3.6 mmol), react at 90 ° C for 3 hours. The reaction solution was cooled to room temperature, quenched with potassium fluoride aqueous solution, stirred for 10 minutes, extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and the solvent was removed by vacuum distillation. Then, it was purified by column chromatography (PE:DCM=1:3 (volume ratio)) to obtain about 467 mg of compound 5-5 with a yield of 77.9%. MALDI-TOF-MS: 399.55.
[0049] Synthesis of compound (5): Accurately weigh compound 5-5 (400 mg, 1 mmol), add it to a 25 ml three-necked flask, add 10 ml of anhydrous 1,4-dioxane to dissolve, replace nitrogen three times, slowly add 3 ml of trimethylsilyl bromide, and then raise the temperature to 70 ° C for 2 hours. Remove excess solvent by vacuum distillation, then add methanol to dissolve the product and transfer it to a beaker, add appropriate amount of water until solid precipitates, stir for 30 minutes and filter. Obtain about 255 mg of compound (5), yield: 74.3%. MALDI-TOF-MS: 343.09.
[0050] Example 4: Synthesis of Compound (6)
[0051] Synthesis of compound 6-1: Accurately weigh compound 5-1 (1.02g, 3mmol), compound 4-1 (25.9g, 120mmol), add tetrabutylammonium bromide (97mg, 0.3 mmol), 8ml 50% potassium hydroxide aqueous solution into a 100ml three-necked flask, replace nitrogen three times, raise the temperature to 70℃, and react for 3 hours. After the reaction solution is cooled to room temperature, it is poured into water for quenching, extracted with ethyl acetate, and the organic phase is distilled under reduced pressure to remove excess solvent. The crude product is purified by column chromatography (PE:EA=8:1 (volume ratio)) to obtain about 1.01g of compound 6-1, with a yield of 70.9%. MALDI-TOF-MS: 476.22.
[0052] Synthesis of compound 6-2: Accurately weigh compound 6-1 (952 mg, 2 mmol), add it to a 25 ml three-necked flask, add 10 ml of triethyl phosphite to dissolve it, and react it in an oil bath preheated to 160°C for 1 hour. Remove triethyl phosphite by vacuum distillation, and then purify it by column chromatography (PE: EA = 1: 2 (volume ratio)) to obtain about 982 mg of compound 6-2, with a yield of 92.1%. MALDI-TOF-MS: 533.34.
[0053] Synthesis of compound 6-3: Accurately weigh compound 6-2 (800 mg, 1.5 mmol) and bistriphenylphosphine palladium dichloride (77 mg, 0.11 mmol) into a 50 ml three-necked flask, add 20 ml toluene and stir to dissolve, replace nitrogen three times, stir to react for 15 minutes, then add compound 5-4 (1.14 g, 3.6 mmol), react at 90 ° C for 3 hours. The reaction solution was cooled to room temperature, quenched with potassium fluoride aqueous solution, stirred for 10 minutes, extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and the solvent was removed by vacuum distillation. Then, it was purified by column chromatography (PE:DCM=1:3 (volume ratio)) to obtain about 485 mg of compound 6-3, with a yield of 75.6%. MALDI-TOF-MS: 427.53.
[0054] Synthesis of compound (6): Accurately weigh compound 6-3 (427 mg, 1 mmol), add it to a 25 ml three-necked flask, add 10 ml of anhydrous 1,4-dioxane to dissolve, replace nitrogen three times, slowly add 3 ml of trimethylsilyl bromide, and then raise the temperature to 70 ° C for 2 hours. Remove excess solvent by vacuum distillation, then add methanol to dissolve the product and transfer it to a beaker, add appropriate amount of water until solid precipitates, stir for 30 minutes and filter. Obtain about 289 mg of compound (6), yield: 77.8%. MALDI-TOF-MS: 371.68.
[0055] Example 5: Synthesis of Compound (7)
[0056] Synthesis of compound 7-2: Accurately weigh compound 7-1 (1.07g, 3mmol), compound 3-2 (22.6g, 120mmol), add tetrabutylammonium bromide (97mg, 0.3 mmol), 8ml 50% potassium hydroxide aqueous solution into a 100ml three-necked flask, replace nitrogen three times, raise the temperature to 70℃, and react for 3 hours. After the reaction solution is cooled to room temperature, it is poured into water for quenching, extracted with ethyl acetate, and the organic phase is distilled under reduced pressure to remove excess solvent. The crude product is purified by column chromatography (PE:EA=15:1 (volume ratio)) to obtain about 1.12g of compound 7-2 with a yield of 80.3%. MALDI-TOF-MS: 464.53.
[0057] Synthesis of compound 7-3: Accurately weigh compound 7-2 (929 mg, 2 mmol), add it to a 25 ml three-necked flask, add 10 ml of triethyl phosphite to dissolve it, and react it in an oil bath preheated to 160 ° C for 1 hour. Remove triethyl phosphite by vacuum distillation, and then purify it by column chromatography (PE: EA = 1: 2 (volume ratio)) to obtain about 922 mg of compound 7-3, with a yield of 88.4%. MALDI-TOF-MS: 521.37
[0058] Synthesis of compound 7-4: Accurately weigh compound 7-3 (782 mg, 1.5 mmol) and bistriphenylphosphine palladium dichloride (77 mg, 0.11 mmol) into a 50 ml three-necked flask, add 20 ml toluene and stir to dissolve, replace nitrogen three times, stir and react for 15 minutes, then add compound 5-4 (1.14 g, 3.6 mmol), and react at 90 ° C for 18 hours. The reaction solution was cooled to room temperature, quenched with potassium fluoride aqueous solution, stirred for 10 minutes, extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and the solvent was removed by vacuum distillation. Then, it was purified by column chromatography (PE:DCM=1:3 (volume ratio)) to obtain about 486 mg of compound 7-4 with a yield of 78.1%. MALDI-TOF-MS: 415.64
[0059] Synthesis of compound (7): Accurately weigh compound 7-4 (416 mg, 1 mmol), add it to a 25 ml three-necked flask, add 10 ml of anhydrous 1,4-dioxane to dissolve, replace nitrogen three times, slowly add 3 ml of trimethylsilyl bromide, and then raise the temperature to 70 ° C for 2 hours. Remove excess solvent by vacuum distillation, then add methanol to dissolve the product and transfer it to a beaker, add appropriate amount of water until solid precipitates, stir for 30 minutes and filter. Obtain about 273 mg of compound (7), yield: 75.9%. MALDI-TOF-MS: 359.85.
[0060] Example 6: Synthesis of Compound (8)
[0061] Synthesis of compound 8-1: Accurately weigh compound 7-1 (1.07g, 3mmol), compound 4-1 (25.9g, 120mmol), add tetrabutylammonium bromide (97mg, 0.3 mmol), 8ml 50% potassium hydroxide aqueous solution into a 100ml three-necked flask, replace nitrogen three times, raise the temperature to 70℃, and react for 3 hours. After the reaction solution is cooled to room temperature, it is poured into water for quenching, extracted with ethyl acetate, and the organic phase is distilled under reduced pressure to remove excess solvent. The crude product is purified by column chromatography (PE:EA=5:1 (volume ratio)) to obtain about 1.16g of compound 8-1, with a yield of 78.4%. MALDI-TOF-MS: 492.32.
[0062] Synthesis of compound 8-2: Accurately weigh compound 8-1 (985 mg, 2 mmol), add it to a 25 ml three-necked flask, add 10 ml of triethyl phosphite to dissolve it, and react it in an oil bath preheated to 160 ° C for 1 hour. Remove triethyl phosphite by vacuum distillation, and then purify it by column chromatography (PE: EA = 1: 2 (volume ratio)) to obtain about 904 mg of compound 8-2, with a yield of 82.3%. MALDI-TOF-MS: 549.38
[0063] Synthesis of compound 8-3: Accurately weigh compound 8-2 (824 mg, 1.5 mmol), bistriphenylphosphine palladium dichloride (77 mg, 0.11 mmol) were added to a 50 ml three-necked flask, 20 ml of toluene was added and stirred to dissolve, nitrogen was replaced three times, and the reaction was stirred for 15 minutes, and then compound 5-4 (1.14 g, 3.6 mmol) was added, and the reaction was carried out at 90 ° C for 18 hours. The reaction solution was cooled to room temperature, quenched with potassium fluoride aqueous solution, stirred for 10 minutes, extracted with ethyl acetate, dried over anhydrous magnesium sulfate, and the solvent was removed by vacuum distillation. Then, it was purified by column chromatography (PE:DCM=1:3 (volume ratio)) to obtain about 528 mg of compound 8-3, with a yield of 79.3%. MALDI-TOF-MS: 443.78
[0064] Synthesis of compound (8): Accurately weigh compound 8-3 (444 mg, 1 mmol), add it to a 25 ml three-necked flask, add 10 ml of anhydrous 1,4-dioxane to dissolve, replace nitrogen three times, slowly add 3 ml of trimethylsilyl bromide, and then raise the temperature to 70 ° C for 2 hours. Remove excess solvent by vacuum distillation, then add methanol to dissolve the product and transfer it to a beaker, add appropriate amount of water until solid precipitates, stir for 30 minutes and filter. Obtain about 290 mg of compound (8), yield: 74.9%. MALDI-TOF-MS: 387.16.
[0065] Preparation and characterization of organic solar cell devices Application Example 1 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (compound (3) was dissolved in methanol solution with a concentration of 0.2 mg / mL) was spin-coated at 2500 rpm for 20 seconds. The hole selection layer was heated on a hot stage at 110°C for 15 minutes to cause a cross-linking reaction to obtain a hole selection layer. The device was then transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (donor material PM6 and acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 with a total concentration of 16 mg / mL, and 0.3% by volume CN was added as an additive) was spin-coated on the hole selection layer at 3000 rpm for 30 seconds. The photoactive layer was then annealed on a hot stage at 90°C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain a structure as shown in Figure 1 Shown is an organic solar cell of ITO / compound (3) / PM6:BTP-eC9 / PDINN / Ag.
[0066] Application Example 2 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (compound (4) was dissolved in methanol solution at a concentration of 0.2 mg / mL) was spin-coated at a speed of 2500 rpm for 20 seconds. The hole selection layer was heated on a hot stage at 110°C for 15 minutes to cause a cross-linking reaction to obtain a hole selection layer. The device was then transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (donor material PM6 and acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 to a total concentration of 16 mg / mL, and 0.3% by volume CN was added as an additive) was spin-coated on the hole selection layer at a speed of 3000 rpm for 30 seconds. Then, the device was annealed on a hot stage at 90°C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain an organic solar cell with a structure of ITO / compound (4) / PM6:BTP-eC9 / PDINN / Ag.
[0067] Application Example 3 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (compound (5) was dissolved in methanol solution at a concentration of 0.2 mg / mL) was spin-coated at a speed of 2500 rpm for 20 seconds. The hole selection layer was heated on a hot stage at 110°C for 15 minutes to cause a cross-linking reaction to obtain a hole selection layer. The device was then transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (donor material PM6 and acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 to a total concentration of 16 mg / mL, and 0.3% by volume CN was added as an additive) was spin-coated on the hole selection layer at a speed of 3000 rpm for 30 seconds. Then, the device was annealed on a hot stage at 90°C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain an organic solar cell with a structure of ITO / compound (5) / PM6:BTP-eC9 / PDINN / Ag.
[0068] Application Example 4 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (compound (6) was dissolved in methanol solution at a concentration of 0.2 mg / mL) was spin-coated at 2500 rpm for 20 seconds. The hole selection layer was heated on a hot stage at 110°C for 15 minutes to cause a cross-linking reaction to obtain a hole selection layer. The device was then transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (donor material PM6 and acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 to a total concentration of 16 mg / mL, and 0.3% by volume CN was added as an additive) was spin-coated on the hole selection layer at 3000 rpm for 30 seconds. The device was then annealed on a hot stage at 90°C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain an organic solar cell with a structure of ITO / compound (6) / PM6:BTP-eC9 / PDINN / Ag.
[0069] Application Example 5 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (compound (7) was dissolved in methanol solution at a concentration of 0.2 mg / mL) was spin-coated at 2500 rpm for 20 seconds. The hole selection layer was heated on a hot stage at 110°C for 15 minutes to cause a cross-linking reaction to obtain a hole selection layer. The device was then transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (donor material PM6 and acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 to a total concentration of 16 mg / mL, and 0.3% by volume CN was added as an additive) was spin-coated on the hole selection layer at 3000 rpm for 30 seconds. The device was then annealed on a hot stage at 90°C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain an organic solar cell with a structure of ITO / compound (7) / PM6:BTP-eC9 / PDINN / Ag.
[0070] Application Example 6 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (compound (8) was dissolved in methanol solution at a concentration of 0.2 mg / mL) was spin-coated at 2500 rpm for 20 seconds. The solution was then heated on a hot stage at 110°C for 15 minutes to cause a cross-linking reaction to obtain a hole selection layer. The device was then transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (donor material PM6 and acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 to a total concentration of 16 mg / mL, and 0.3% by volume CN was added as an additive) was spin-coated on the hole selection layer at 3000 rpm for 30 seconds. The solution was then annealed on a hot stage at 90°C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain an organic solar cell with a structure of ITO / compound (8) / PM6:BTP-eC9 / PDINN / Ag.
[0071] Comparative application example 1 The glass sheet coated with strip ITO (anode) was ultrasonically treated with alkali solution, deionized water, acetone, isopropanol, and ethanol for 20 minutes in sequence. The cleaned ITO glass was dried and then treated with ozone for 20 minutes. Then, the hole selection layer solution (the compound (Ref) was dissolved in a methanol solution with a concentration of 0.2 mg / mL) was spin-coated at a speed of 2500 rpm for 20 seconds, and then annealed on a hot stage at 80 °C for 10 minutes to obtain a hole selection layer; then the device was transferred to a glove box with a nitrogen atmosphere, and the prepared photoactive layer solution (the donor material PM6 and the acceptor material BTP-eC9 were dissolved in chloroform at a mass ratio of 1:1.2 with a total concentration of 16 mg / mL, and 0.3% CN by volume was added as an additive) was spin-coated on the hole selection layer at a speed of 3000 rpm for 30 seconds, and then annealed on a hot stage at 90 °C for 10 minutes to obtain a photoactive layer. Then, an electron transport layer is spin-coated on the photoactive layer, wherein the electron transport layer material is selected from PDINN, and then a 110 nm thick silver electrode is deposited on the electron transport layer by vacuum evaporation to obtain an organic solar cell with a structure of ITO / compound (Ref) / PM6:BTP-eC9 / PDINN / Ag.
[0072]
[0073] The prepared organic solar cell device was subjected to a performance test under sunlight. T80 means that the organic solar cell device was placed in an N2 glove box and continuously illuminated with an LED light source. A multi-channel solar cell attenuation test system was used to apply an mpp (maximum power point) corresponding load to both ends of the device to keep it in a continuous working state. The device performance was measured every 10 minutes, and the time (T80) required for the device's photoelectric conversion efficiency to drop to 80% of its initial value was measured. Details are shown in Table 1.
[0074] Table 1 T80 data of different organic solar cells in application examples Serial number Hole transport materials T80 (h) Application Example 1 Compound (3) 395 Application Example 2 Compound (4) 356 Application Example 3 Compound (5) 349 Application Example 4 Compound (6) 366 Application Example 5 Compound (7) 346 Application Example 6 Compound (8) 371 Comparative application example 1 Compound (Ref) 167 It can be seen from the data in Table 1 that the vinyl-containing hole transport material according to the present invention can form a uniform and stable film by cross-linking. Compared with the device prepared by the non-vinyl-containing hole transport material in device comparison example 1, its device life T80 is greatly improved. Figure 2 The T80 curves of Application Example 1 (Compound (3)) and Comparative Application Example 1 (Compound (Ref)) also show that the battery prepared from the self-assembled material containing vinyl groups of the present invention has higher photoelectric performance stability and longer device life.
[0075] The above examples further illustrate the content of the present application, but should not be construed as limiting the present application. Without departing from the spirit and substance of the present application, modifications and replacements made to the methods, steps or conditions of the present application all fall within the scope of the present application. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.
Claims
1. A self-assembling material containing vinyl, characterized in that: The self-assembly material has a structure as shown in formula (I): (I) in: n is selected from 0, 1, 2, 3, 4, 5 or 6; -Z- is selected from the group consisting of absence, a single bond, -O-, -S-, or CR1R2; R1 and R2 are independently selected from -H, -D, and an alkyl group having 1 to 6 carbon atoms.
2. The self-assembly material containing vinyl according to claim 1, characterized in that n is selected from 1 or 3.
3. The self-assembly material containing vinyl according to claim 1, characterized in that -Z- is selected from absence, a single bond, -O-, -S- or C(CH3)2.
4. The self-assembly material containing vinyl according to claim 1, characterized in that R1 and R2 are independently selected from -H, -D, methyl, ethyl, n-propyl, isopropyl, n-butyl or tert-butyl.
5. The self-assembly material containing vinyl according to claim 1, characterized in that The self-assembly material is selected from any one of the following structures: 。 6. An organic solar cell, comprising at least one hole selection layer, characterized in that: The hole selection layer material comprises the vinyl-containing self-assembly material according to any one of claims 1-5.
7. An organic solar cell, comprising an anode layer, a hole selection layer, a photoactive layer, an electron transport layer and a cathode layer stacked in sequence from bottom to top, characterized in that: The material of the hole selection layer is selected from the vinyl-containing self-assembly material according to any one of claims 1-5.
8. The organic solar cell according to claim 7, characterized in that The material of the anode layer is selected from FTO or ITO; The photoactive layer comprises a donor material and an acceptor material, wherein the donor material is preferably selected from one or more of PBDB-T, PM6, PM7, D18, D18-Cl, PBQx-Cl, and PTQ10, and the acceptor material is selected from Y6, L8-BO, N3, BTP-eC9, PC 61 BM, PC 71 One or more of BM; The material of the electron transport layer is selected from one or more of PDINN, PDINO, PFN-Br, PNDIT-F3N-Br or PNDIT-F3N; The cathode layer material is selected from one or more alloys of zinc, silver, aluminum, gold and nickel.
9. A method for preparing an organic solar cell, characterized in that: Includes steps: Step 1, cleaning the conductive glass containing the anode layer; Step 2, dissolving the vinyl-containing self-assembly material according to any one of claims 1 to 5 in an organic solvent to prepare a hole selection layer solution, evenly spin-coating the hole selection layer solution on a conductive glass containing an anode layer, and allowing the reaction to stand at 100-150° C. for 5-20 minutes to obtain a hole selection layer; Step 3, spin coating a photoactive material on the surface of the hole selection layer under an inert atmosphere to prepare a photoactive layer, and annealing; Step 4: Spin coating the electron transport layer material on the photoactive layer to obtain the electron transport layer; Step 5: Under a vacuum environment, a cathode material is evaporated on the surface of the electron transport layer to obtain a cathode layer, and the organic solar cell is obtained by packaging.
10. Use of the organic solar cell according to any one of claims 6 to 8 in automobiles, buildings or Internet of Things devices.
Citation Information
Patent Citations
Crosslinkable hole-transport material with vinyl as well as preparation method and application of crosslinkable hole-transport material
CN107118333A
Non-fused electron acceptor material, preparation method and organic solar cell formed by non-fused electron acceptor material
CN109438415A
Compound, liquid crystal composition and liquid crystal display
CN112812014A
Halogen-containing hole transport material, application and perovskite battery
CN116574130A
Self-assembled monomolecular layer hole transport material based on diphenylamine and synthesis method and application thereof
CN116655682A